Samuelsonian economics and the twenty-first century - Szenberg, Michael; Ramrattan, Lall, 1951-; Gottesman, Aron A. (Oxford University Press, 2006)
This volume illuminates and critically assesses Paul A. Samuelson's voluminous and groundbreaking contributions to the field of economics. The volume includes contributions from eminent scholars, including six Nobel Laureates, covering the extraordinary depth and breadth of Samuelson's contributions.